2010
DOI: 10.1038/sj.bjc.6605622
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of survival in patients with brain metastases from cutaneous melanoma

Abstract: BACKGROUND: This retrospective study aimed to identify prognostic factors in patients with brain metastases from cutaneous melanoma. METHODS: In all, 265 patients under regular screening according to valid national surveillance guidelines were included in the study. Kaplan -Meier analyses were performed to estimate and to compare overall survival. Cox modeling was used to identify independent determinants of the overall survival, which were used in explorative classification and regression tree analysis to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
95
2
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 31 publications
14
95
2
12
Order By: Relevance
“…Table VI presents the values of average survival periods of patients with MBM depending on the KPS score, which were 5.9-6.3 months for KPS ≥ 70 and were definitely lower in patients with a poorer general performance (KPS < 70), where they varied from 1.8 to 3.8 months. The results based on the site's material are comparable with those presented with other authors [5,13,14,37,40,46]. The other, generally accepted prognostic factor is the number of MBM foci.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Table VI presents the values of average survival periods of patients with MBM depending on the KPS score, which were 5.9-6.3 months for KPS ≥ 70 and were definitely lower in patients with a poorer general performance (KPS < 70), where they varied from 1.8 to 3.8 months. The results based on the site's material are comparable with those presented with other authors [5,13,14,37,40,46]. The other, generally accepted prognostic factor is the number of MBM foci.…”
Section: Discussionsupporting
confidence: 80%
“…Staudt et al claim that relatively good prognoses can only be made in patients with a single metastatic focus [40]. Rades et al in turn, distinguishes two groups of patients: with 1-3 MBM foci and with more than 3 MBM foci; and Weltman and Sperduto propose breaking down the patient groups into 3 categories: with 1, with 2-3 and more than 3 MBM [32,34,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A recent large study of almost 700 patients diagnosed with melanoma brain metastases found a mean survival time of less than 5 months. 3 Melanoma metastasizing to the central nervous system is not unexpected considering that during development neural crest cells are the precursor cells for melanocytes, where melanoma originates. 4 Additionally, one of the common findings in melanoma is neuronal tracking, and it has been suggested that this may be related to expression of the proto-oncogene RET.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, some key modifiers of survival were not reported, including pretreatment levels of lactate dehydrogenase, hemorrhage within the metastatic tumor bed, recursive partitioning analysis class, and status of systemic disease at treatment onset. 2,5,7 One last important unknown is any deEditorial finitive inclusion and exclusion criteria qualifying a patient for ipilimumab therapy. Notwithstanding these limitations, all inherent to a retrospective review, the impressive survival differences argue for aggressive prospective evaluation of ipilimumab in patients with Stage IV melanoma with cerebral metastases.…”
mentioning
confidence: 99%